The role of social context in own body size estimations: An investigation of the body schema. (March 2022) - Aniulis, Ellie; Nicholls, Michael E.R.; Thomas, Nicole A.; Sharp, Gemma
Abstract: Women tend to overestimate their body size, including space needed to pass through gaps/apertures. These results were generated using static apertures resembling doorways. However, body image is influenced by other bodies around us, and how estimations of passability may be influenced by social context is unknown. To investigate, a series of apertures were created comprising two women facing each other, with the space between creating the 'doorway'. The apertures were created using either two larger-bodied or two smaller-bodied women. Non-social versions were generated using the social aperture silhouettes. Thirty-four undergraduate women viewed a series of apertures – varying in width relative to their own size – and judged whether they believed they could pass through them. State and trait body dissatisfaction measurements were also taken. Point of subjective equality (PSE) data suggested that participants did not overestimate the space needed to pass through apertures overall, but showed an overestimation of space for the larger-bodied social doorways. Correlations suggested higher levels of state body dissatisfaction associated with higher PSEs, but only in the social conditions. Results showed that participants may have been engaging in different mechanisms regarding social versus non-social doorways, and the importance of social context when investigating own body size estimations. Highlights: We used a unique methodology to measure body size estimations. Women overestimated space required to pass through larger-bodied social apertures. Viewing smaller-bodied social apertures induced greater state body dissatisfaction. Results demonstrate the importance of social context in body image research.